Dual en bloc technique for adult renal transplantation. Issue 8 (21st July 2017) - Tran, Kim Chi; Li, David; Taqi, Ali; Sener, Alp; McAlister, Vivian C.; Luke, Patrick P.
Abstract: Introduction: We describe and provide follow‐up for a novel simplified technique permitting dual en bloc (DEB) transplantation of adult organs using single in situ arterial and venous anastomoses. Methods: Twenty‐two adult DEB transplants were performed at our center between 2001 and 2012, utilizing 44 kidneys en bloc. Results were compared with 20 solitary transplants from expanded criteria donors (ECD) associated with lower terminal serum creatinines and Remuzzi biopsy scores vs DEB group. Adult DEB implants had donor inferior vena cava connected to recipient external iliac vein and "Y" arterial interposition graft anastomosed to the recipient iliac artery. Ureters were conjoined prior to implantation as a single patch into the recipient bladder. Results: Mean operative time was 206±57 minutes in DEB vs 180±30 minutes in single transplants ( P <.05). Delayed graft function rate was 23% vs 25% in both groups. At 12‐month follow‐up, mean serum creatinine was 152±66 μmol/L vs in 154±52 μmol/L DEB and single kidney transplant recipients, respectively ( P =NS). Three‐year overall and graft specific survival were 86% and 84% in the DEB group, respectively ( P =NS). Complication rates were similar between groups. Conclusions: This DEB renal transplantation technique is safe and effective in adults. By employing techniques used to conjoin organ vasculature ex vivo, the number of in situ anastomoses is reduced, thereby minimizing operative ischemic time and potential for complications associated with extensive vascular dissection.